Price Delegation in Sales Organizations: An Empirical Investigation - Ann-Kristin Hansen; Kissan Joseph; Manfred Krafft (BuR - Business Research, 2008)
The allocation of decision rights is an integral component of designing organizational architecture. Economists have long understood the importance of co-locating decision rights with the knowledge that is valuable to those decisions. Following this prescription, marketing scholars have developed strong theoretical arguments in favor of delegating pricing authority to the sales force. Empirical work, however, reveals a significant number of sales organizations yielding only minimal authority to their salespeople. Given this divergence between theory and practice, we develop and empirically test two mitigating factors that could potentially explain why firms restrict pricing authority. We test our hypotheses on a sample of 222 German sales organizations and find that the data are generally consistent with our conceptualization.
urn:nbn:de:0009-20-13948
Keywords: 650; pricing authority; delegation; determinants of price delegation; pricing; sales force management; Preismanagement; Verkaufspersonal; Empirische Methode; Prinzipal-Agent-Theorie; Operations Research